SME Managers and Financial Literacy - Eniola, Anthony A.; Harry, Entebang (SAGE Publications, 2017)
The aim of this study is to examine the level of small and medium enterprises (SMEs) business owners-managers' financial literacy and its impact on firm's performance. The article applied a random sample and structural equation modelling (SEM) approaches in assessing the influence of SME business owners-managers' level of financial literacy within the three states in the southwest Nigeria. The findings show the complete effect of business owner-manager's financial knowledge, financial awareness and financial attitude in converting financial literacy to increase in firm performance. Also, they confirm that financial knowledge and awareness of SME business owners-managers are obviously not a prerequisite for the performance of SMEs, but entrepreneur characteristics in decision-making and relationship to financial attitude have a comparison with financial literacy. The research limitation evolves from cross section information observation that solely covers the southwestern part of the country. Additionally, inspired to meet the analysis gap is panel data analysis. Training courses through strategic orientation on the attitudinal perception of SME business owner-manager and basic business management skills, capacity-building aspect, leadership development as well as networking via relationship marketing and management on financial literacy may have significant effect on SMEs' performance and growth for the managers in general in Nigeria. The article is one of the first to examine the level of financial literacy of SME business owners-managers in Nigeria. The article therefore sets an important benchmark for further research in this area.